Structural and active site modification studies implicate Glu, Trp and Arg in the activity of xylanase from alkalophilic Bacillus sp (NCL 87-6-10) - Balakrishnan, H.; Satyanarayana, L.; Gaikwad, S. M.; Suresh, C. G. (Enzyme and Microbial Technology, 2006)
Structural studies and residue modification using group specific reagents were used to ascertain the role of different functional groups in xylanase from alkalophilic Bacillus sp. (NCL 87-6-10). Treatment with N-bromosuccinimide resulted in fast enzyme inactivation. Reaction with Woodward's reagent K resulted in initial fast followed by slower inactivation. In both cases enzyme was protected against inactivation by the substrate, xylan. The reaction of the enzyme with phenylglyoxal has revealed one essential arginine residue at the active site. The three-dimensional structural analysis of the xylanase at 2.8 angstrom resolution also implicates involvement of Trp, and Arg residues and carboxylate groups in the binding of substrate and in the catalysis of xylanase. (c) 2005 Published by Elsevier Inc.
Keywords: active-site residues; alkaline xylanase; Chemical modification; three-dimensional structure

Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Steady state and time-resolved fluorescence studies of a hemagglutinin from Moringa oleifera - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (Journal of Fluorescence, 2008)
The saccharide binding and conformational characterization of a hemagglutinin, a low molecular weight protein from the seeds of Moringa oleifera was studied using steady state and time resolved fluorescence. The lectin binds sugars LacNAc (K-a = 1380 M-1) and fructose (K-a = 975 M-1), as determined by the fluorescence spectroscopy. It has a single tryptophan per monomer which is exposed on the surface and is in a strong electropositive environment as revealed by quenching with iodide. Quenching of the fluorescence by acrylamide involved both static (K-s = 0.216 M-1) and collisional (K-sv= 8.19 M-1) components. The native protein showed two different lifetimes, tau(1) (1.6 ns) and tau(2) (4.36 ns) which decrease and get converted into a single one, (2.21 ns) after quenching with 0.15 M acrylamide. The bimolecular quenching constant, k(q) was 7.55 x 10(11) M-1 s(-1). ANS binding studies showed that the native protein has exposed hydrophobic patches which get further exposed at extreme acidic or alkaline pH. However, they get buried in the interior of the protein in presence of 1 M GdnHCl or urea.
Keywords: ANS binding; fluorescence; Hemagglutinin; lifetime; Moringa oleifera; saccharide binding; Solute quenching

Structure-activity relationship of a hemagglutinin from Moringa oleifera seeds - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2008)
The hemagglutinin from the seeds of Moringa oleifera (MoL) agglutinates human as well as rabbit erythrocytes; the affinity for the latter is almost 250 times more than that for the former. MoL was inhibited by glycoproteins namely thyroglobulin, fetuin and holotransferin indicating the complex sugar specificity of the lectin. The protein is a homodimer with molecular mass of 14 kDa, subunits (7.1 kDa) linked by the disulfide bond(s). The secondary structure elements of MoL area-helix, 28%; beta-sheet, 23%; turn 20% and unordered 28%. While the activity and secondary structure were not affected at extreme pH and high temperature, they were drastically affected in presence of dithiothreitol at and above pH 7.0, indicating that disulfide linkages hold the active conformation of the protein. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: disulfide linkages; Moringa oleifera hemagglutinin; Secondary structure

Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase

Structure of highly active BSH enzyme with subordinated post-translational excision - Chand, Deepak; Panigrahi, Priyabrata; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Bile salt hydrolase; Mutagenesis; X-ray crystallography

Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C. G. (Journal of Industrial Microbiology & Biotechnology, 2015)
Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in beta-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans (PdPGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted PdPGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans. Experimental data showed that PdPGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, PdPGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in PdPGA, which upon mutation selectively could improve the thermostability of the enzyme.
Keywords: Alkalistable; beta-lactam antibiotics; Consensus approach; Disulfide bridge; Ion pairs; Penicillin acylase; Thermostability

Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase

Structure and function of a highly active Bile Salt Hydrolase (BSH) from Enterococcus faecalis and post-translational processing of BSH enzymes - Chand, D. (Biochim Biophys Acta., 2018)
Bile Salt Hydrolase (BSH), a member of Cholylglycine hydrolase family, catalyzes the de-conjugation of bile acids and is evolutionarily related to penicillin V acylase (PVA) that hydrolyses a different substrate such as penicillin V. We report the three-dimensional structure of a BSH enzyme from the Gram-positive bacteria Enterococcus faecalis (EfBSH) which has manifold higher hydrolase activity compared to other known BSHs and displays unique allosteric catalytic property. The structural analysis revealed reduced secondary structure content compared to other known BSH structures, particularly devoid of an anti-parallel β-sheet in the assembly loop and part of a β-strand is converted to increase the length of a substrate binding loop 2. The analysis of the substrate binding pocket showed reduced volume owing to altered loop conformations and increased hydrophobicity contributed by a higher ratio of hydrophobic to hydrophilic groups present. The aromatic residues F18, Y20 and F65 participate in substrate binding. Thus, their mutation affects enzyme activity. Docking and Molecular Dynamics simulation studies showed effective polar complementarity present for the three hydroxyl (-OH) groups of GCA substrate in the binding site contributing to higher substrate specificity and efficient catalysis. These are unique features characteristics of this BSH enzyme and thought to contribute to its higher activity and specificity towards bile salts as well as allosteric effects. Further, mechanism of autocatalytic processing of Cholylglycine Hydrolases by the excision of an N-terminal Pre-peptide was examined by inserting different N-terminal pre-peptides in EfBSH sequence. The results suggest that two serine residues next to nucleophile cysteine are essential for autocalytic processing to remove precursor peptide. Since pre-peptide is absent in EfBSH the mutation of these serines is tolerated. This suggests that an evolution-mediated subordination of the pre-peptide excision site resulted in loss of pre-peptide in EfBSH and other related Cholylglycine hydrolases.
Keywords: autocatalytic processing; Bile salt hydrolase; molecular dynamics; Mutagenesis; Polar complementarity; X-ray crystallography

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin